Evaluation of Digital Terrain Model (DTM) Accuracy Using Terrestrial Laser Scanning (TLS) in Flat and Steep Topographies - Atri Febriyanto; Thoriq Zein Munajat; Yudo Prasetyo; Muhammad Adnan Yusuf (Jurnal Geosains dan Remote Sensing, 2025)
The advancement of geospatial technology has enabled various methods to produce high-accuracy Digital Terrain Models (DTMs), including Terrestrial Laser Scanning (TLS). This study evaluates the accuracy of TLS-derived DTMs in areas with varying topography at Universitas Diponegoro, Semarang. Data collection involved TLS, Total Station, and Leveling for georeferencing and accuracy assessment. The analysis included DTM visualization, RMSEz and LE90 calculations, and paired t-tests. Results show the TLS-derived DTM meets Class 1 accuracy standards for a 1:1000 map scale. Visualization demonstrated TLS's ability to represent both steep and flat terrain in detail, including contours and breaklines. The statistical test yielded a p-value of 0.710, indicating no significant difference between TLS and terrestrial data. The evaluated accuracy metrics are essential for assessing the reliability of TLS in real-world mapping. The results confirm TLS's capability to produce consistent and detailed terrain models, supporting its use in high-precision spatial applications such as infrastructure planning, environmental monitoring, and disaster mitigation. Therefore, TLS is a reliable method for generating high-quality DTMs across diverse topographic conditions.